Me, myself, and them - Snyder, Kurt (Oxford University Press, 2007)
In Me, Myself, and Them, Kurt, now an adult, looks back from the vantage point of recovery and eloquently describes the debilitating changes in thoughts and perceptions that took hold of his life during his teens and twenties. As a memoir, this book is remarkable for its unvarnished look at the slow and difficult process of coming back from severe mental illness. Yet Kurt's memoir is only half the story. With the help of psychiatrist Raquel E. Gur, M.D., Ph.D., and veteran science writer Linda Wasmer Andrews, Kurt paints the big picture for others affected by adolescent schizophrenia. Drawing on the latest scientific and medical evidence, he explains how to recognize warning signs, where to find help, and what treatments have proved effective. Kurt also offers practical advice on topics of particular interest to young people, such as suggestions on managing the illness at home, school, and work, and in relationships with family and friends